Victory Monument: the Politics of Representations of Thai Identity and Colonial Discourse in Built Forms - Koompong Noobanjong (My University, 2018)
This research presents a critical inquiry of the Victory Monument in Bangkok with respect to its symbolicroles in the mediation of state power, together with the identification of the “Thai Self,” known as khwampenthaior ‘Thainess.’ By utilizing Thainess as a mode of problematization, the paper argues that: 1) under theideological cover of nationalism, anti-colonialism, and democracy, the politics of representation at the memorialhave lent legitimacy for governments since the Pibunsongkhram era to pursue their political agenda; and 2) thepractice of colonization in Southeast Asia did not exclusively come from the West, but also took place amongstates within the region, as evidenced by the construction of the Victory Monument. In fostering self-reflexivedialogues on Thainess, the upcoming investigations illustrate the ways in which the built environment has beenemployed to represent something other than itself in the nation-building process. These topics are discussedvia the themes of: 1) a political form of architecture and urban space: how the Victory Monument has beenmanipulated to serve politics; and 2) an architectural and urban form of politics: how politics has influenced thedesign and signification of the memorial.
Keywords: Southeast Asian Sociopolitical Studies